Peningkatan Keterampilan Sosial Peserta Didik SMA Menggunakan Layanan Bimbingan Kelompok Dengan Teknik Diskusi - Maharani, Laila; Masya, Hardiyansyah; Janah, Miftahul (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2018)
The problem in the research is the low social skill of the learners. The problem in this research is "what is group guidance service with effective discussion technique to improve low social skill to class XII student of IPA 2, IPA 5 and IPS 1, IPS 2 SMA Negeri 7 Bandar Lampung academic year 2016/2017?". The purpose of this research is to know that group counseling service with an effective discussion technique to improve low social skill in class XII student of IPA 2, IPA 5 and IPS 1, IPS 2 SMA Negeri 7 Bandar Lampung academic year 2016/2017. The method used in this research is quasi experimental method with pretest-posttest control group design design. Subjects in the study amounted to 20 students class XII IPA and IPS SMA Negeri 7 Bandar Lampung who have low social skills. Data collection techniques in this study using a questionnaire, namely a questionnaire (scale of social skills). The results obtained in this study indicate that social skills can be improved using group counseling services with discussion techniques, it is shown from the results of data analysis using t-test, from the scores obtained experiment and control class that is tcount = 2.678> ttable = 2.101 then, Ho is rejected and Ha accepted, which means group guidance services with effective discussion techniques to improve low social skills. Brief conclusions in this study that group guidance services with effective discussion techniques to improve the social skills of student class XII SMA Negeri 7 Bandar Lampung academic year 2016/2017